Long-term mortality and prehospital tirofiban treatment in patients with ST elevation myocardial infarction - Fabris, Enrico; Giannitsis, Evangelos (Heart, 2017)
Objective We undertook a subgroup analysis of the On-TIME 2 (Ongoing Tirofiban In Myocardial infarction Evaluation 2), a placebo-controlled, double-blind, randomised trial, in order to evaluate the association between N-terminal pro-B-type natriuretic peptide (NT-proBNP) levels and long-term (5 years) mortality and to investigate the effect of prehospital tirofiban administration on mortality in relation to NT-proBNP levels. Methods; A total of 984 patients with ST elevation myocardial infarction (STEMI) undergoing primary percutaneous coronary intervention (PCI) were randomised to either in ambulance tirofiban or placebo. NT-proBNP levels were evaluated on admission before angiography (baseline) and 18-96 hours thereafter (post PCI). Results: There were 918 (93.3%) patients with NT-proBNP values available at baseline and 865 (87.9%) post PCI. Patients with baseline NT-proBNP values above the median (137 pg/mL) had higher 30-day (5.1% vs 0.2%, p<0.001), 1-year (7.0% vs 0.7%, p<0.001) and 5-year (20.3% vs 4.9%, p<0.001) mortality as compared with patients with values below the median. Using multivariate Cox analysis, NT-proBNP above the median was an independent predictor for 5-year mortality (HR 2.73, 95% CI 1.47 to 5.06; p=0.002). Patients with values above the median who received early tirofiban treatment had significant lower mortality compared with patients treated with placebo at 30 days (2.7% vs 7.5%, p=0.021) and 1 year (4.5% vs 9.4%, p=0.043). At 5 years, a lower but non-significant mortality rate was maintained in the treatment group (18% vs 22.4%, p=0.265). Conclusions: In patients with STEMI, baseline NT-proBNP level independently predicts long-term mortality. In patients with baseline NT-proBNP levels above the median, early prehospital treatment with tirofiban significantly reduced 30-day and 1-year mortality, suggesting that high-risk patients may derive particular benefit. This finding should be confirmed in other studies. Trial registration number ISRCTN06195297.
Gesehen am 12.11.2018